2021
DOI: 10.1007/s10143-021-01602-5
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical aspects of the insula, opercula and peri-insular white matter for a transcortical approach to insular glioma resection

Abstract: The insula is a lobe located deep in each hemisphere of the brain and is surrounded by eloquent cortical, white matter, and basal ganglia structures. The aim of this study was to provide an anatomical description of the insula and white matter tracts related to surgical treatment of gliomas through a transcortical approach. The study also discusses surgical implications in terms of intraoperative brain mapping. Five adult brains were prepared according to the Klingler technique. Cortical anatomy was evaluated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…The insula, surrounded by cortical gyrus, white matter, and basal ganglia structures ( Dziedzic et al, 2022 ), is a center of integration for emotional, visceromotor, autonomic, and interoceptive information. Its diverse functional roles may be due to its strong connections to a broad network of cortical and subcortical regions ( Wang R. et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The insula, surrounded by cortical gyrus, white matter, and basal ganglia structures ( Dziedzic et al, 2022 ), is a center of integration for emotional, visceromotor, autonomic, and interoceptive information. Its diverse functional roles may be due to its strong connections to a broad network of cortical and subcortical regions ( Wang R. et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Functional brain imaging studies revealed significant changes in the FC in the cerebellum-neocortex and cerebellum-basal ganglia circuits in patients with MDD ( Dai et al, 2022 ). Additionally, an increased long-range positive FC (lpFC) in the left inferior parietal lobule was found to distinguish HCs and patients with MDD ( Dziedzic et al, 2022 ). Given that the architecture of the connectome affects the effectiveness and velocity of information transport, including regions such as anterior and middle cingulate cortex, medial occipital areas, superior frontal areas, post- and precentral gyrus, parahippocampal gyrus, and precuneus, the balance of intra-hemispheric and inter-hemispheric connectivity plays a crucial role in brain function ( Krupnik et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Intracranial abscesses are treated with surgical drainage followed by long-term antibiotic treatment. [ 9 , 10 ] Surgical drainage is preferably accomplished by stereotactic needle aspiration. [ 9 - 12 ] If needle aspiration fails to decompress the abscess or if the abscess recurs, surgical excision of the abscess may be required.…”
Section: Discussionmentioning
confidence: 99%
“…For this type of procedure, the AF constitutes the deep, superior, and posterior functional limit of resection (Dziedzic et al, 2022).…”
Section: Af Topographical Anatomy and Surgical Implicationsmentioning
confidence: 99%